Demonstration of microfiber hybrid Mach–Zehnder and knot resonator structure - Sulaiman, A. (John Wiley & Sons, 2013)
We demonstrate a microfiber hybrid structure consisting of a microfiber knot resonator (MKR) and a microfiber Mach–Zehnder interferometer (MMZI) by micro-manipulating a microfiber. The microfiber used has a waist diameter of 1 μm and is fabricated using a flame brush technique. The hybrid structure generates dual resonances spectrum, which combines a characteristic resonant of MKR and MMZI. The MMZI resonant exhibits a much higher free spectral range (FSR) of 3.1 nm with the extinction ratio of 3 dB. The MKR resonant has a FSR of 0.24 nm and extinction ratio of 5 dB.